Evaluation of the potential of mobile phone specific electromagnetic fields (UMTS) to produce micronuclei in human glioblastoma cell lines. (April 2017) - Al-Serori, Halh; Kundi, Michael; Ferk, Franziska; Mišík, Miroslav; Nersesyan, Armen; Murbach, Manuel; Lah, Tamara T.; Knasmüller, Siegfried
Abstract: Some epidemiological studies indicate that mobile phones cause glioblastomas in humans. Since it is known that genomic instability plays a key role in the etiology of cancer, we investigated the effects of the universal mobile telecommunications system radiofrequency (UMTS-RF) signal, which is used in "smart" phones, on micronucleus (MN) formation and other anomalies such as nuclear buds (NBUDs) and nucleoplasmatic bridges (NPBs). MN are formed by structural and numerical aberrations, NBs reflect gene amplification and NPBs are formed from dicentric chromosomes. The experiments were conducted with human glioblastoma cell lines, which differ in regard to their p53 status, namely U87 (wild-type) and U251 (mutated). The cells were cultivated for 16 h in presence and absence of fetal calf serum and exposed to different SAR doses (0.25, 0.50 and 1.00 W/kg), which reflect the exposure of humans, in presence and absence of mitomycin C as former studies indicate that RF may cause synergistic effects in combination with this drug. We found no evidence for induction of MN and other anomalies. However, with the highest dose, induction of apoptosis was observed in U251 cells on the basis of the morphological features of the cells. Our findings indicate that the UMTS-RF signal does not cause chromosomal damage in glioblastoma cells; the mechanisms which lead to induction of programmed cell death will be investigated in further studies. Highlights: Aim was to find out if mobile phone specific radiation causes chromosomal damage. The effect of the UMTS signal was tested in two human glioblastoma cell lines. No induction of micronuclei and several other nuclear anomalies were found. Induction of programmed cell death was observed in a p53 mutated cell line (U251). In p53 proficient cells (U87) the apoptosis rate was not increased.